Water consumption, wastewater generation and characterization of a slaughterhouse for resource conservation and recovery. Issue 1 (10th December 2021) - Shende, Akshay D.; Dhenkula, Swati; Waghambare, Ashish; Rao, Neti Nageswara; Pophali, Girish R.
Abstract: This study is an overview of a beef-based slaughterhouse's processes and operations, from animal reception to product dispatch, including water consumption over 105 days. On average, 1, 114 L/buffalo is required for slaughter and processing. Corresponding wastewater generation is between 916 and 1, 089 L. Water consumption per buffalo decreases with increasing numbers of buffalos slaughtered per day, and in some operations – e.g., plant washing, personal hygiene, canteen, and knife and instrument washing – is independent of the number of buffalo slaughtered. In contrast, refrigeration depends partly on the numbers slaughtered. Wastewater characterization from each slaughterhouse process and operation was carried out over three months, and wastewater physico-chemical characteristics from individual operations are presented. HIGHLIGHTS: Wastewater obtained from different slaughtering processes/operations has wide variation in characteristics in terms of SS, O &G, COD & BOD. Conventionally, wastewater is treated from all slaughtering operations in a combined manner. Segregation of various streams is highly recommended for treatment and potential resource recovery. Graphical Abstract